Preparation of Carboxymethyl Chitosan Microspheres and Their Application in Hemostasis. (4th December 2015) - Liu, Lu; Lv, Qi; Zhang, Qingyun; Zhu, Hui; Liu, Wei; Deng, Guiru; Wu, Yuqiang; Shi, Chaofeng; Li, Hui; Li, Lingzhi
Abstract: Objective: Chitosan (CS) is currently used as a hemostatic agent in emergencies and in military settings. However, its application is limited owing to its poor hydrophilia at neutral pH. Carboxymethyl chitosan (CMCS) is an important, water-soluble derivative of CS. In this study, we prepared CS and CMCS microspheres (CSMs and CMCSMs, respectively) and evaluated their hemostatic effect. Methods: To prepare the microspheres of various sizes, we used the emulsion cross-linking technique. CMCSMs were also loaded with etamsylate (DIC). Clotting time in vitro and in a hepatic injury model was examined to evaluate the hemostatic effect. Results: CMCSMs swelled more and clotted faster than did CSMs. CMCSMs loaded with DIC had no effect on hemostasis. Conclusions: Both increasing material hydrophilicity and expanding the contact area promoted clotting, whereas chemical cross-linking hampered it because of decreased swelling. CMCSMs are promising candidates for the production of effective hemostatic agents. ( Disaster Med Public Health Preparedness . 2017;11:660–667)